Argumentum ad Ignorantiam: Smartphone-Connected Listening Devices - Maidment, David W.; Amlani, Amyn M. (Seminars in Hearing, 2020)
In this article, we review the current literature assessing the application and benefits of connected hearing technologies, as well as their potential to improve accessibility to and affordability of hearing healthcare. Over the past decade, there has been a proliferation of hearing devices that connect wirelessly to smartphone technologies via Bluetooth. These devices include (1) smartphone-connected hearing aids that must be obtained from a licensed audiologist or hearing aid dispenser; (2) direct-to-consumer devices, such as personal sound amplification products; and (3) smartphone-based hearing aid applications (or apps). Common to all these connected devices is that they permit the user to self-adjust and customize their device programs via an accompanying smartphone app. There has been a growing body of literature assessing connected hearing devices in adults living with hearing loss. Overall, the evidence to date supports the notion that all connected hearing devices can improve accessibility to and affordability of amplification. It is unclear, however, whether connected technologies are a clinically effective alternative to traditional hearing aids. Even so, the impact of connectivity is especially pertinent given the sudden disruption caused by the recent global COVID-19 pandemic, whereby connected technologies enable patients to receive treatment through mobile-based, tele-audiology platforms.
Keywords: hearing aids; hearing loss; personal sound amplification products; smartphone; applications